The Choice of Surgical Tactics in The Treatment Of Recurrent Goiter Diving for The Trachea (Texas Journal of Medical Science, 2024)
According to the review article, there have been 52 occurrences of complications observed in the postoperative period following 478 strumectomies conducted over the last decade. These complications primarily involve the trachea and stem from the complex surgical procedure of modifying the thyroid in the presence of nodules or cysts. It is important to note that these complications often exhibit a recurring nature. Significant focus is given to delineating the procedure's technique, concurrently emphasizing the significance of considering the relevant anatomical characteristics of the neck when mobilizing the thyroid gland. It is crucial to recognize the importance of attending to essential aspects during the separation of each layer. Measures taken to avoid injuries to neighboring organs due to complications that may occur during surgery are described in detail. Detailed explanations are provided to patients regarding the procedures and recommendations to be followed during the postoperative period. The report encompasses essential information including conclusions and key recommendations pertaining to thyroid gland, recurrent laryngeal nerve, and thyroid surgery.